Praktik Green Accounting dan Nilai Perusahaan: Peran Mediasi Sustainability Report pada Sektor Energi dan Mineral di Indonesia - Anis Nur Rohmah; Merry Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research examines how green accounting influences firm value, both directly and indirectly through sustainability reporting, in energy and mineral sector companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. The measurement of green accounting and sustainability reporting was carried out using content analysis, while firm value was assessed through Tobin’s Q. A quantitative research design was applied, using purposive sampling for sample selection. Based on the predetermined criteria, 37 companies were selected, producing 111 firm-year observations. The data were analyzed using the Random Effect Model (REM). The findings show that green accounting significantly affects both firm value and sustainability reporting. In contrast, sustainability reporting does not significantly affect firm value and is unable to mediate the relationship between green accounting and firm value. These results indicate that investors in the energy and mineral sectors tend to give greater attention to actual environmental practices than to sustainability disclosures alone. Therefore, strengthening the implementation of green accounting may serve as an important strategy for companies to improve their value in the capital market.